Лирика русских поэтов - Магидсон С. М. (1991)
Экземпляры: Селтинская районная библиотека (ч/з) (20180723) / Инвентарный номер: 167744 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 48 / ББК: 84(2Рос=Рус)1